Effect of Virtual Laboratory Instruction on Secondary School Biology Students’ Achievement in Kwali Area Council, Abuja, Nigeria (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The study investigated the “Effect of Virtual Laboratory Instruction on Senior Secondary School Students’ Achievement in Biology in Kwali Area Council of F.C.T”. The study adopted the quasi-experimental pre-test/post-test control group design. The sample in the study consisted of 78 senior secondary school II Biology students selected from two Local Government Area using purposive sampling techniques. The students in the experimental group were exposed to virtual laboratory strategy while the control group was taught Biology with the conventional method. The instrument used in the study was Biology Achievement Test (BAT) to collect data for the study. The reliability coefficients of the study was obtained using Kuder-Richardson for BAT with the value of 0.86. Data were analyzed using mean and standard deviation to answer the two research questions while t-test was used to test the two null hypotheses generated for the study at 0.05 level of significance. Findings revealed that, there was significant difference in the mean achievement scores of secondary school students taught Biology using virtual laboratory strategy as against their counterparts taught biology using the conventional method. However, there was no significant differences in the mean achievement scores of male and female students taught Biology using virtual laboratory. Therefore, recommendations were made among others that teachers should be adequately trained in the use of educational technologies. Workshops, seminars, and continuous professional development programs should be organized to equip biology teachers with the skills necessary to incorporate virtual labs into their instructional practices effectively.